Les universités interculturelles au Mexique - Sylvia Schmelkes (Les éditions de la Maison des sciences de l'Homme, 2008)
This paper describes the creation project of Intercultural Universities in Mexico and suggests an analysis of the results obtained, the difficulties met and the challenges set up for the first nine intercultural universities put in place between 2004 and 2007. It shows that this experience is meant to be either a way of improving equity in higher education by encouraging a better representation of native people among the number of university students, or an effort to strengthen and reassert the value of indigenous cultures by promoting its diffusion through research and dialogues with other cultures.